Concentration of selected elements in the hair of Madagascar girls in relation to nutritional status and place of residence. Issue 10 (28th November 2022) - Zielińska-Dawidziak, Magdalena; Czlapka-Matyasik, Magdalena; Wojciechowska, Zofia; Proch, Jędrzej; Niedzielski, Przemysław
Abstract : Abstract: Although the children malnutrition in Madagascar and the environmental pollution of this country has been widely discussed, there is no research on the differences in toxic elements accumulation in human body in dependence on nutritional status of Malagasy. Nine elements concentration (Al, As, Cd, Cr, Hg, Ni, Pb, Sn and Sb) was determined in scalp hair of 103 schoolgirls (8–15 years old), living in two areas: urban – close to Antananarivo (UR) and rural Berevo region (RU). Samples were analysed by an inductively coupled plasma optical emission spectrometer. The nutritional status was evaluated by Cole's index. Underweight was related to higher accumulation of Al, Cd and Cr in the hair girls, and more common among girls living in RU than UR region (42 % v . 28 %). Two-factor ANOVA showed differences in the Al and Cr content in the girls' hair depending both on their place of residence and nutritional status. This indicates additional consequence of malnutrition to the girls development and health.